Local perceptions of HIV risk and prevention in Southern Zambia - Byron, Elizabeth; Gillespie, Stuart; Hamazakaza, Petan (International Food Policy Research Institute, 2006)
The HIV prevention strategies and programs that are widely promoted in sub-Saharan Africa in large part target HIV awareness and individual behavioral modification – conventionally through the ABC (Abstain, be Faithful and use Condoms) approach to prevention. Yet barriers remain to the successful implementation of such strategies at the individual-level. In order to implement effective policy and programs approaches to curb the AIDS epidemic, it is essential that greater consideration be given to the reality of what is happening on the ground in terms of risk behavior. Within the economic and social climate, this includes customs and tradition, gender norms of behavior, and levels and types of resource access and control. More focused attention is needed on how people actually behave or perceive the issues of susceptibility, risk and HIV spread, and what they are doing to avoid infection.